Digital Accounting Interventions: Securing SME Financial Sustainability through Mind, Emotion, and Capability - Amir Hamzah; Dendi Purnama; Siti Nuke Nurfatimah (Universitas Sultan Ageng Tirtayasa, 2026)
Financial sustainability has become a critical challenge for Small and Medium-sized Enterprises (SMEs) in the digital economy, where entrepreneurs are required not only to manage financial resources effectively but also to adapt to rapidly evolving digital financial technologies. Although previous studies have extensively examined financial literacy, technology adoption, and financial behaviour, limited research has integrated cognitive, psychological, and digital capability factors within a single framework to explain SMEs' financial sustainability. Addressing this gap, this study investigates the effects of Mental Accounting Accuracy, AIS Anxiety, and Digital Financial Literacy on the Financial Sustainability of SMEs. Drawing upon Behavioral Accounting Theory, the Technology Acceptance Model (TAM), and the Dynamic Capability perspective, the study develops an integrated behavioural–technology framework to explain sustainable financial outcomes. Data were collected through a structured questionnaire administered to 130 SME owners and managers in Kuningan Regency, Indonesia, and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that Mental Accounting Accuracy and Digital Financial Literacy have significant positive effects on Financial Sustainability, whereas AIS Anxiety has a significant negative effect. These results indicate that SMEs achieve greater financial sustainability when entrepreneurs possess strong cognitive financial capabilities, high digital financial competence, and lower levels of anxiety toward accounting information systems. The study contributes to the literature by integrating cognitive, emotional, and digital capability perspectives into a unified model of SMEs' financial sustainability, thereby extending the application of Behavioral Accounting Theory and the Technology Acceptance Model in the context of digital financial management.